North African and Omani Ibâḍî Accounts of the Munâẓâra: A Preliminary Comparison - Adam Gaiser (Revue des Mondes Musulmans et de la Méditerranée)
This chapter compares Western/North African and Eastern/Omani Ibâḍî accounts of the munâẓara (debate) that took place at Ḥarûrâ’ before the Battle of Nahrawân to reveal two similar yet distinct traditions. A further comparison with non-Ibâḍî (i.e. al-Ṭabarî, al-Balâdhurî, al-Baghdâdî, etc.) versions of the debate shows that it is the Western/North African tradition that shares certain features and narrative structures with non-Ibâḍî accounts. The key to understanding these particular textual configurations is the figure of the last Basran Imâm, Abû Sufyân Maḥbûb Ibn al-Raḥîl. Abû Sufyân wrote his Kitâb Abî Sufyân on the commission of the Rustumid Imâm Aflaḥ Ibn ‘Abd al-Wahhâb, and likely incorporated Basran and Kûfan Ibâḍî traditions that did not gain wide currency among Ibâḍîs in Oman. For this reason, non-Ibâḍî and Western munâẓara accounts share certain characteristics that are not present in Eastern accounts, even though Oman is geographically closer to the places where non-Ibâḍî accounts likely originated.